2010
DOI: 10.1007/s12519-010-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in infants younger than 3 months: a single center’s experience

Abstract: Infants aged 3 months or younger may suffer from intussusception and most of them present with typical symptoms. Early diagnosis and treatment are needed for a good prognosis. Intrauterine intussusception may be an etiological factor for ileal atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
2
Order By: Relevance
“…[4][5][6][7] Similarly, the causes of intussusceptions documented in the study were in keeping with those of other series. [25,26] In conclusion, the accuracy of US diagnosis in experienced hands was high and could increase the diagnostic confidence in patients with suspected intussusceptions. Thickened bowel wall in other gastrointestinal conditions could produce US features of intussusceptions.…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][7] Similarly, the causes of intussusceptions documented in the study were in keeping with those of other series. [25,26] In conclusion, the accuracy of US diagnosis in experienced hands was high and could increase the diagnostic confidence in patients with suspected intussusceptions. Thickened bowel wall in other gastrointestinal conditions could produce US features of intussusceptions.…”
Section: Discussionmentioning
confidence: 96%
“…Infants younger than 3 months rarely suffer from this disease, and the treatment in this age group is mentioned less in the international literature and is a challenge for the clinician. The article by Kong et al [2] adds further information to clinical presentations and management of intussusception in infants younger than 3 months.…”
Section: Fei-teng Kong and Yun-man Tangmentioning
confidence: 99%
“…Although it is widely accepted that strenuous physical activity may trigger bronchial constriction in asthmatic children, appropriate exercise has been proven beneficial to asthmatic children. [1] Unfortunately, in China, asthmatic children and their parents, teachers, and doctors are rarely aware of these benefits and still hold negative views of exercise. In a recent issue of the World Journal of Pediatrics, Cheng et al [2] reported a significantly lower participation in physical activity among asthmatic children than healthy controls, which provided useful information for understanding the exercise status of asthmatic children in China.…”
Section: Correspondencementioning
confidence: 99%
“…To the Editor I have read with great interest the article by Kong et al [1] where the authors refer to a successful pneumatic reduction of acute intestinal intussusception in 17/23 cases (74% [95%CI 56-92]). The article makes no mention of whether the machine of air/barium enema utilized for the intussusception's reduction is connected to the patient by means of an occlusive catheter.…”
Section: Controlled Insuffl Ation Of Air For Diagnosis and Treatment mentioning
confidence: 99%
See 1 more Smart Citation